Zmienność rozkładów stóp zwrotu portfeli Markowitza w porównaniu z portfelami o minimalnej semiwariancji - Rutkowska-Ziarko, Anna; Markowski, Lesław (Time variability of distributions of Markowitz's portfolios returns in comparison with minimum semi-variance portfolios returns, 2006)
The research indicates efficient portfolios using semi-variance as a risk measure and Markowitz’s ones. Changeability of distribution of Markowitz’s portfolios returns and minimum Semi-variance portfolios were compared. The data used in the analysis refer to the period from 02.01.2000 to 30.12.2005. The selected, basic parameters of returns distribution were calculated. Generally the portfolios returns are non-normally distributed. The analysis of empirical results suggests that target semi-variance is a more appropriate measure of risk than variance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 446-452